DEVELOPMENT OF MOBILE ECG APPLICATION TO IMPROVE ECG INTERPRETATION SKILLS OF GENERAL PRACTITIONERS AND MEDICAL STUDENTS - Rizki Amalia Gumilang; Anis Fuad; Vita Arfiana Nurul Fatimah; Shofuro Hasana; Orisativa Kokasih; Putrika Prastuti Ratna Gharini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
ABSTRACT Background: Electrocardiogram (ECG) has become a crucial examination in the management of cardiac emergencies. Accordingly, improvement of ECG interpretation skills is mandatory for general practitioners as the front-liners in emergency cases. The Mobile ECG application was developed as mobile learning media to facilitate continuing improvement of ECG interpretation skills.Aims: This study aimed to investigate the impact of the Mobile ECG application toward ECG interpretation skills of general practitioners and medical students and evaluate its usability.Methods: A pilot quasi-experimental study was conducted in a 1-week timeframe using webinar and the Mobile ECG application. Subjects were recruited through consecutive sampling. They met the following criteria: 1) registered as general practitioners or medical students, 2) completed the basic ECG pre and post-tests, and 3) agreed to participate in the study. The Mobile ECG is a web-based application which consists of modules, quizzes, and gallery of ECG interpretations. Pre and post-test analysis and system usability scale (SUS) questionnaire were used to evaluate the impact and usability of the application.Results: A total of 252 subjects were recruited and 80.2% were general practitioners. There was a significant increase in post-test scores compared to pre-test (p=0.000) for all subjects. General practitioners significantly gained more score increment than medical students (1.08 vs 0.16, p=0.001). Based on the SUS score of 67.5, the application was marginally accepted by the users.Conclusion: To conclude, the implementation of the Mobile ECG application did improve basic ECG interpretation skills. According to the SUS score, this application still needs improvement.